INTERAKSI TOKOH LAIL DENGAN LINGKUNGAN DALAM NOVEL HUJAN KARYA TERE LIYE: KAJIAN EKOKRITIK SASTRA - Mastura Mastura; Elsa Mulya Karlina (CV. Adiba Aisha Amira, 2025)
Humans and the environment have a close relationship and depend on each other. Along with the development of the times and increasingly sophisticated technology, the interaction between humans and the environment is increasingly intensive, there are many cases that have negative impacts such as ecosystem damage, pollution, and climate change. This research entitled “Lail's character interaction with the environment in the novel Rain by Tere Liye” aims to describe Lail's character interaction with the environment and describe ecological values in the novel. The interaction of other characters is described through various treatments or actions taken by the characters towards the environment that occurred. Meanwhile, ecological values in the novel Hujan by tere Liye with Greg Garrard's theory in the form of values contained in disasters, housing/shelter, and the earth. The method used in this research is a qualitative method with the type of library research. In this case, the research approach that produces data is descriptive data in the form of written data from observations on objects. The results show that the novel Hujan shows the interaction of characters with the environment in dealing with various natural disasters and has ecological values that are beneficial for the sustainability of the lives of living things.